Structural order of water molecules around hydrophobic solutes: length-scale dependence and solute-solvent coupling - Hande, Vrushali R.; Chakrabarty, Suman (Journal of Physical Chemistry B, 2015)
It has been suggested that the structure and thermodynamics of the water molecules in the hydration layer of simple hydrophobic solutes undergo an order disorder transition around a nanometer length-scale of the solute size. Using extensive atomistic molecular dynamics (MD) and replica exchange molecular dynamics (REMD) simulation studies, we have probed this order disorder transition around model hydrophobic solutes of varying size and shape (spherical, planar, and linear), as well as flexible hydrophobic homopolymer chains (n-alkanes), where the conformational fluctuations are likely to create both spatial and temporal heterogeneity on the solvent accessible surface. We have explored the structural response of the water molecules in the hydration shell due to the local variations of the length-scale (or curvature) upon hydrophobic collapse and/or local conformational changes of these polymers. We have shown that the tetrahedral order of the water molecules in the hydration shell is practically independent of the polymer size in the extended state of the polymer due to the availability of a subnanometer cross-sectional length-scale, allowing the water molecules to form hydrogen bonds around the polymer chain. Beyond a certain length of the polymer chains, the collapsed states (associated with larger solute length-scale) start to induce disorder in the surface water molecules. We demonstrate that the local structure (both local number density and tetrahedral order) of the hydration layer is dynamically coupled to the local topology of the polymer. Thus, we envisage that in a flexible (bio)polymer, the hydration shell properties will be sensitive to the local conformational state of the molecule (both spatially and temporally), and the overall observed water structure and dynamics will be dependent on the topological/chemical heterogeneity, and the time-scale of fluctuations in the local curvature (length-scale) of the solvent accessible surface. Moreover, we have demonstrated the direct coupling between the local density fluctuations of water and the local hydrophobic collapse of the polymer. For the extended state of the polymer, the local solvent density fluctuation is practically independent of the solute coordinate (length-scale), and the hydrophobic collapse of the polymer is prompted by a ``local dewetting'' process induced by these fluctuations.

Soluble polybenzimidazoles with intrinsic porosity: synthesis, structure, properties and processability - Kumar, Vikas; Chatterjee, Shyambo; Sharma, Pragati; Chakrabarty, Suman; Avadhani, Chilukuri V.; Sivaram, Swaminathan (56Journal of Polymer Science Part A-Polymer Chemistry, 2018)
We have explored two novel comonomers, namely, 4,16-dicarboxyl[2.2]paracyclophane and 5,5,6,6-tetraamino-3,3,3,3-tetramethyl-1,1-spirobi[indane], for the synthesis of co-polybenzimidazoles (co-PBIs) with intrinsic porosity. Both these monomers possess twisted structures that can lead to awkward macromolecular shapes that cannot pack efficiently. The consequences of introducing these two monomers on the structure and properties of PBIs are reported. The random copolymers synthesized are amorphous and possess glass transition temperatures (T(g)s) greater than 400 degrees C. T-g decreases with increasing comonomer content indicating an increase in fractional free volume. The copolymers have low surface area. TEM and BET measurements show evidence of mesopore formation. The copolymers show significant carbon dioxide adsorption. Single chain molecular dynamics simulation of 24-mer repeat units shows intramolecular void spaces arising as a result of distorted polymer chain with reduced conformational mobility. These studies define a new synthetic strategy for bottoms-up synthesis of PBIs with intrinsic porosity. (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2018, 56, 1046-1057

Size-dependent order-disorder crossover in hydrophobic hydration: comparison between spherical solutes and linear alcohols - Hande, Vrushali; Chakrabarty, Suman (ACS Omega, 2022)
Theory and computer simulation studies have predicted that water molecules around hydrophobic molecules should undergo an order-disorder transition with increasing solute size around a 1 nm length scale. Some theories predict the formation of a clathrate-like ordered structure around smaller hydrophobic solutes (<1 nm) and the formation of disordered vapor-liquid interfaces around larger solutes (>1 nm) and surfaces. Experimental validation of these predictions has often been elusive and contradictory. High-resolution Raman spectroscopy has detected that water around small hydrophobic solutes shows a signature similar to that of bulk water at lower temperature (increased ordering and a stronger hydrogen-bonded network). Similarly, water around larger solutes shows an increasing population of dangling OH bonds very similar to higher temperature bulk water. Thus, the solute size dependence of the structure and dynamics of water around hydrophobic molecules seems to have an analogy with the temperature dependence in bulk water. In this work, using atomistic classical molecular dynamics (MD) simulations, we have systematically investigated this aspect and characterized this interesting analogy. Structural order parameters including the tetrahedral order parameter (Q), hydrogen bond distribution, and vibrational power spectrum highlight this similarity. However, in contrast to the experimental observations, we do not observe any length-dependent crossover for linear hydrophobic alcohols (n-alkanols) using classical MD simulations. This is in agreement with earlier findings that linear alkane chains do not demonstrate the length-dependent order-disorder transition due to the presence of a sub-nanometer length scale along the cross section of the chain. Moreover, the collapsed state of linear hydrocarbon chains is not significantly populated for smaller chains (number of carbons below 20). In the context of our computational results, we raise several pertinent questions related to the sensitivity of various structural and dynamical parameters toward capturing these complex phenomena of hydrophobic hydration.